Effect of process parameters on mechanical properties of AA5052 joints using underwater friction stir welding - Paramaguru, D. (Universiti Malaysia Pahang, 2020)
Underwater Friction Stir Welding (UFSW) is a solid-state joining technique which uses a non-consumable tool to weld metals. The objective of this investigation is to evaluate the mechanical properties of the AA5052 Aluminium alloy joints prepared by UFSW. The effect of different type of welding tools and welding parameters on the weld joint properties are studied. Square, tapered cylindrical and taper threaded cylindrical type of welding tools have been used to produce the joints with the tool rotational speed varying from 500 rpm to 2000 rpm while the welding speed varying from 50 mm/min to 150 mm/min. Tensile strength, micro-hardness distribution, fracture features, micro-and macrostructure of the fabricated weld joints have been evaluated. The effect of welding process parameters that influences the mechanical properties and fracture characterization of the joints are explained in detail. A maximum Ultimate Tensile Strength (UTS) value of 222.07 MPa is attained with a gauge elongation of 14.78. Microstructural evaluation revealed that most of the fracture are found on the thermal mechanically affected zone (TMAZ)adjacent to the weld nugget zone (WNZ) due to bigger grain sizes. It is found that most of the joints exhibit ductile characteristics in failure. Fractography analysis has been used to find the behavior of weld joints in failure. Â© The Authors 2020. Published by Penerbit UMP.